Oxygen-rich tetrahedral surface phase on high-temperature rutile VO2(110)(T) single crystals - Wagner, Margareta; Planer, Jakub; Heller, Bettina; Langer, Jens; Limbeck, Andreas; Boatner, Lynn A.; Steinrück, Hans-Peter; Redinger, Josef; Maier, Florian; Mittendorfer, Florian; Schmid, Michael; Diebold, Ulrike (Physical Review Materials, 2021)
Vanadium dioxide undergoes a metal-insulator transition from an insulating (monoclinic) to a metallic (tetragonal) phase close to room temperature, which makes it a promising functional material for many applications, e.g., as chemical sensors. Not much is known about its surface and interface properties, although these are critical in many applications. In this paper, we present an atomic-scale investigation of the tetragonal rutile VO2(110)(T) single-crystal surface and report results obtained with scanning tunneling microscopy, low-energy electron diffraction, and x-ray photoelectron spectroscopy, supported by density-functional-theory-based calculations. The surface reconstructs into an oxygen-rich (2 x 2) superstructure that coexists with small patches of the underlying unreconstructed (110)-(1 x 1) surface when the crystal is annealed >600 degrees C. The best structural model for the (2 x 2) surface termination, conceptually derived from a vanadium pentoxide (001) monolayer, consists of rings of corner-shared tetrahedra. Over a wide range of oxygen chemical potentials, this reconstruction is more stable than the unreconstructed (110) surface and models proposed in the literature.
CRIS-Team WoS Importer:2021-12-17